New distributional records and life stage description of Caenis species (Ephemeroptera: Caenidae) from Brazil - Lima, Lucas R. C.; Boldrini, Rafael (Zootaxa, 2017)
The genus Caenis Stephens, 1835 is well represented in South America with 24 recorded species (14 in Brazil). Based on additional material from Brazil, we describe for the first time the nymphal and egg stages of C. reissi, and re-describe the eggs of C. cuniana. New distributional records for these species and Caenis elidioi are given, and C. teipunensis (previously described from Venezuela) is reported for the first time from Brazil.